Brain Derived Neurotrophic Factor Levels in Aged Rats Post-Systemic Human Mesenchymal Stem Cell Administration - dwijayanti, adisti (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
Brain-Derived Neurotrophic Factor (BDNF) levels were affected by aging. Brain BDNF levels were known to decrease along with advanced age thus correlated with any diseases such as cognitive impairment and Alzheimer. Mesenchymal Stem Cell (MSC) is one of the potential modalities actively investigated against age-related diseases. This study evaluated the effect of human MSC administration to brain BDNF levels in aged rats. Intravenous injection of 10 million per body weight human MSC were given four times in 3 months interval to 22-24 months old female and male Spraque–Dawley rats. As control group, aged rats were injected by normal saline at the same volume and frequencies. Moreover, young 3-6 months rats also examined as negative control. By the end of the experiment, we analyzed three rats from each group. Brain BDNF levels were measured by enzyme-linked immunosorbent assay and normalize to the protein levels. One-way ANOVA and LSD post hoc analysis was performed to compare the differences between groups. BDNF levels in male appeared similar between young, aged, and MSC treated groups. Meanwhile, control aged female groups had significantly lower BDNF levels compared to young (p = 0.019) and MSC-treated aged rats (p = 0.001). There was no difference of BDNF levels between young and MSC-treated aged in female rats (p = 0,068). Both sex had similar BDNF levels (p = 0.249) in control-aged groups. In contrast, female young and MSC-treated aged rats achieved significantly higher BDNF levels (p = 0.009 and p <0.001) compared to the male groups, respectively. These results suggest that human mesenchymal stem cell intravenous injection can increase brain BDNF levels in female aged rats.